Pesantren-Based Higher Education Institutions: The Format of Modern Islamic Education - Mashudi Mashudi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aimed to describe and formulate the format of pesantren-based higher education institutions on the aspects of the scientific structure and management at the University of Nurul Jadid Probolinggo and the University of Ibrahimy Situbondo. The data were collected through observation, interviews, and review of documents. Data analysis was performed by reducing data, presenting data, and drawing conclusions. The validity of the data used member check, source, and triangulation method. The results of the study revealed that the pesantren-based higher education institutions had characteristics in scientific integration, such as students had to stay in the boarding school, studied the kitab kuning and join Madrasah Diniyah, and took special compulsory subjects. In the management aspect, the recruitment of educators was based on skills and qualifications, as well as the ability to recite the Qur'an. In terms of higher education policy, the Rector has the highest position but still consults the boarding school caretakers regarding the policies that will be carried out.